التوافق الزواجي و علاقته بالعوامل الخمسة الكبرى للشخصية عند أساتذة التعليم الثانوي - ماكور, طيب (جامعة الوادي - University of Eloued, 2021)
تهدف الدراسة الحالية إلى دراسة التوافق الزواجي وعلاقته بالعوامل الخمسة الكبرى للشخصية لدى عينة من أساتذة التعليم الثانوي. وقد تم الاعتماد على المنهج الوصفي من خلال اختيار عينة قصدية، من بعض ثانويات مدينة البليدة قوامها 170 زوج وزوجة من الاساتذة بمرحلة التعليم الثانوي. وقد تم استخدام استمارة لجمع البيانات ثم تم تطبيق مقياس التوافق الزواجي، ومقياس العوامل الخمسة الكبرى للشخصية بعد التأكد من الخصائص السيكومترية للمقياسين. وبعد جمع المعطيات وفقا للخطوات المنهجية للبحوث العلمية، وحسابها ببرنامج الحزمة الإحصائية للعلوم الاجتماعية وصلت الدراسة إلى النتائج التالية: - لا توجد فروق ذات دالة إحصائية بين متوسطات درجة عصابية للأزواج المتوافقين وغير المتوافقين. - توجد فروق دالة إحصائيا بين متوسطات درجة سمة الانبساطية للأزواج المتوافقين وغير المتوافقين لصالح مجموعة الغير متوافقين زواجيا. - توجد فروق دالة إحصائيا بين متوسطات درجات سمة الطيبة للأزواج المتوافقين وغير المتوافقين لصالح مجموعة المتوافقين زواجيا. - لا توجد فروق دالة إحصائيا بين متوسطات درجة سمة التفتح على الخبرة للأزواج المتوافقين يكاد يتساوى مع متوسط درجات سمة التفتح على الخبرة للأزواج غير المتوافقين. - توجد فروق دالة إحصائيا بين متوسطات درجات سمة يقظة الضمير للأزواج المتوافقين وغير متوافقين لصالح مجموعة المتوافقين. - لا توجد فروق بين المجموعات في متوسط درجات التوافق تبعا لعدد الأطفال. - توجد فروق دالة بين مجموعات عينة البحث وفقا لمتغير مدة الزواج. Abstract: The present study aims to study marital compatibility and its relationship to the five major factors of personality in a sample of secondary education teachers. The descriptive approach was relied upon by selecting an intentional sample from some secondary schools in the city of Blida, consisting of 170 husbands and wives from teachers in the secondary education stage. A questionnaire was used to collect data, then the marital compatibility scale was applied, and the scale of the five major factors of personality after confirming the psychometric properties of the two scales. After collecting data according to the methodological steps of scientific research, and computing them with the Statistical Package for Social Sciences (SPSS) program, the study reached the following results: There are no statistically significant differences between the averages of the neurotic score of the compatible and incompatible couples. There are statistically significant differences between the mean scores of the extroverted trait of the compatible and incongruent couples in favor of the heterosexual group. There are statistically significant differences between the mean scores for the kindness trait of compatible and incompatible couples in favor of the marital group. There are no statistically significant differences between the means of the experience trait score for the compatible spouses. There are statistically significant differences between the mean scores of the conscientiousness trait of the compatible and incompatible couples in favor of the compatible group. There were no differences between groups in the mean scores of agreement according to the number of children. There are significant differences between the research sample groups according to the variable of the duration of marriage
مقال
Keywords: التوافق الزواجي ; العوامل الخمسة الكبرى للشخصية; Marital compatibility; The Big Five Factors of Personality